Glacial δ13C decreases in the western South Atlantic forced by millennial changes in Southern Ocean ventilation ... : جليدي δ 13 </ sup> C ينخفض في غرب جنوب المحيط الأطلسي بسبب التغيرات الألفية في تهوية المحيط الجنوبي ... - Marília de Carvalho Campos; Cristiano Mazur Chiessi; Ines Voigt; Alberto Piola; Henning Kuhnert; Stefan Mulitza (OpenAlex, 2016)
Abstract. Abrupt millennial–scale climate change events of the last deglaciation (i.e., Heinrich Stadial 1 and the Younger Dryas) were accompanied by marked increases in atmospheric CO2 presumably originated by outgassing from the Southern Ocean. However, information on the preceding Heinrich Stadials during the last glacial period is scarce. Here we present stable carbon isotopic data (δ13C) from two species of planktonic foraminifera from the western South Atlantic that reveal major decreases (up to 1 ‰) during Heinrich Stadials 3 and 2. These δ13C decreases are most likely related to millennial–scale periods of intensification in Southern Ocean deep water ventilation presumably associated with a weak Atlantic meridional overturning circulation. After reaching the upper water column of the Southern Ocean, the δ13C depletion would be transferred equatorward via central and thermocline waters. Together with other lines of evidence, our data are consistent with the hypothesis that the CO2 added to the ... : الملخص. كانت أحداث تغير المناخ المفاجئة على نطاق الألفية في التآكل الأخير (أي هاينريش ستاديال 1 ودرياس الأصغر) مصحوبة بزيادات ملحوظة في ثاني أكسيد الكربون في الغلاف الجوي التي يُفترض أنها نشأت عن إطلاق الغازات من المحيط الجنوبي. ومع ذلك، فإن المعلومات عن ملاعب هاينريش السابقة خلال الفترة الجليدية الأخيرة نادرة. نقدم هنا بيانات نظائر الكربون المستقرة (δ 13C) من نوعين من المنخربات العوالق من غرب جنوب المحيط الأطلسي والتي تكشف عن انخفاضات كبيرة (تصل إلى 1 ‰) خلال ملاعب هاينريش 3 و 2. من المرجح أن تكون هذه الانخفاضات في δ 13C مرتبطة بفترات التكثيف على نطاق الألفية في تهوية المياه العميقة في المحيط الجنوبي والتي يُفترض أنها مرتبطة بدوران انقلابي ضعيف في المحيط الأطلسي. بعد الوصول إلى عمود المياه العلوي للمحيط الجنوبي، سيتم نقل استنزاف δ 13 C باتجاه خط الاستواء عبر المياه المركزية والخط الحراري. جنبًا إلى جنب مع خطوط الأدلة الأخرى، تتوافق بياناتنا مع الفرضية القائلة بأن ثاني أكسيد الكربون المضاف إلى الغلاف الجوي خلال أحداث تغير المناخ المفاجئة على نطاق الألفية خلال الفترة الجليدية الأخيرة نشأ أيضًا في المحيط ووصل ...